1,2,4-Triazine Analogs as Novel Class of Therapeutic Agents - Kumar, Rajeev; Sirohi, T.S.; Singh, Hariram; Yadav, Ramji; Roy, R.K.; Chaudhary, A.; Pandeya, S.N. (Mini Reviews in Medicinal Chemistry, 2014)
1,2,4-Triazine nucleus is a prominent structural core system present in numerous pharmacologically active compounds. Till date, various 1,2,4-triazine analogs, possesing a wide range of potent pharmacological activities, have been reported. This review is an attempt to compile the medicinal chemistry aspects of various synthesized 1,2,4-triazine analogs reported so far.
Keywords: antimicrobial activity